Sytuacja dydaktyczna z perspektywy kompetencji komunikacyjnych nauczycieli akademickich - Jakubczak-Chodźko , Magdalena (Kultura-Społeczeństwo-Edukacja, 2018)
Jakubczak-Chodźko Magdalena, Sytuacja dydaktyczna z perspektywy kompetencji komunikacyjnych nauczycieli akademickich [The didactic situation from the perspective of academic teacher communication skills]. Kultura – Społeczeństwo – Edukacja nr 2(14) 2018, Poznań 2018, pp. 111–117, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.9. This article shows a mode of perception of the relevant didactic situation from the perspective of teacher-held communicatio skills. Using the analysis of rationality, presented are new areas of perception of teacher competence. In addition, with the aid of the approach presented by Jürgen Habermas, it was possible to analyse the significance of communication skills as key in the teaching profession.